Analysis of heterogeneity in cardiology systematic reviews published be-tween 2000-2005 and 2011-2016 - Aranzazu Ceballos, Andrés David; Marín Cárdenas, Juan Sebastián; Gallego González, Daniel; Donado Gómez, Jorge Hernando (Medicina UPB, 2023)
Introduction: cardiology is one of the medical specialties with the most systematic reviews and meta-analyses. Studying the methodology of the reviews and analyzing their statistical heterogeneity is essential to guarantee their scientific validity. Objective: to describe the comparison of association measures, statistical models and degree of heterogeneity in meta-analyses of systematic reviews of pharmacological interventions in cardiology, published between 2000-2005 and 2011-2016. Methodology: analytical study based on the description and comparison of statistical methods of systematic reviews of pharmacological interventions in cardiology, published in the Cochrane library. For the qualitative variables, absolute and relative frequencies were estimated, while for the quantitative ones, means and standard deviations, or medians and interquartile ranges, were determined, depending on their distribution. The Student’s t test was used to establish the difference in means and the Chi square for the difference in proportions. Results: 54 systematic reviews were included, with a total of 1.053 meta-analyses, 6 reviews with 240 meta-analyses between 2000-2005, and 48 reviews with 813 meta-analyses between 2011-2016. Most meta-analyses used standard treatment as the comparison group (56.6%), measured nominal qualitative outcomes (86.3%), determined relative risks (63.3%), and applied fixed-effect models (57.8%). In the 2011-2016 period, an average of the Higgins Index was found to be 17.5 lower than in the 2000-2005 (p<0.05). Conclusion: there was evidence of a decrease in statistical heterogeneity and an increase in the implementation of random effects models, which accounts for greater rigor when it comes to demonstrating truly significant results.